Volcanic activity and its link to glaciation cycles : Single-grain age and geochemistry of Early to Middle Miocene volcanic glass from ANDRILL AND-2A core, Antarctica - R. Nyland; K. Panter; S. Rocchi; G. Di Vincenzo; P. Del Carlo; B. Field; P. Gorsevski; M. Tiepolo (Journal of Volcanology and Geothermal Research, 2013)
In the frame of the ANtarctic DRILLing Program, volcanic glass fragments were collected from the AND-2A core between similar to 354 and 765 m below sea floor (mbsf) as accumulations (5-70 vol.%) within sediments. Here, we present the physical characteristics, age and geochemistry of the glass, which enable us to reconstruct Early to Middle Miocene volcanic activity in southern McMurdo Sound and, for the first time, document the response of volcanism to climate change in Antarctica. Glass-rich sediments include muddy-to-fine sandstone and stratified diamictite. Glass varies in color, size, vesicularity, crystal content, angularity, and degree of alteration. The mostly fresh glass exhibits delicate cuspate forms indicating deposition as primary ash fall. Ar-40-Ar-39 age determinations on individual glass grains are in good agreement with the depositional age model of the sediments (ca. 15.6 to 18.6 Ma), supporting for most of them a primary origin, however, some samples do contain older fragments that indicate glass recycling during times of enhanced glacial erosion. Most glasses are mafic (MgO=3 to 9 wt.%) and vary from hypersthene to nepheline normative with a restricted range in SiO2 (45.2 0.8 wt.%, 1 sigma) and trace element concentrations typical of the rift-related alkaline rocks in the Erebus Volcanic Province. The glass extends known composition of early phase Mount Morning activity (ca. 11-19 Ma), the only known Early to Middle Miocene source, to a more mafic end, revealing a previously unknown explosive, strongly alkaline, basaltic phase and the most primitive forms of both strongly alkaline (basanite to phonolite) and moderately alkaline (alkali basalt to trachyte) magma associations. The glass-rich sediments occur in glacimarine sequences that record 56 cycles of glacial advance and retreat. Volcanic response to glacial cyclicity is observed both physically and geochemically in AND-2A glass. Higher glass volumes in sediments correlate with ice minimum conditions between 300 and 800 mbsf Ratios of Ba to ...